1996
DOI: 10.1177/000494419604000104
|View full text |Cite
|
Sign up to set email alerts
|

Education and Poverty: An Australian Primary School Case Study

Abstract: This paper documents some mechanisms and relationships evident in a multicultural, working-class Brisbane primary school which ensure that ‘children from poor families are, generally speaking, the least successful by conventional methods and the hardest to teach by conventional methods’ (Connell, 1993, p.I). Chief among them are three survival strategies commonly used by teachers in the face of the daily difficulties. Each of these, it is demonstrated, contributes to lack of academic success for many students … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

1998
1998
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 9 publications
0
7
0
2
Order By: Relevance
“…From its origins in anthropology, the notion of bricolage has proved useful in an extremely broad range of scholarly fields. Disciplines invoking use of Levi-Strauss's insights include-not surprisingly-anthropology (Chao, 1999;Dumont, 1996) and sociological ethnography (Denzin and Lincoln, 1994;Katovich, 1995;Weinstein and Weinstein, 1991), but also political science (Lanzara, 1998); women's studies (Gray, 1982), interpersonal relationships (Conville, 1997), complex information systems design (Lanzara, 1999), legal studies (Hull, 1991;Tushnet, 1999), education (Dent and Hatton, 1996;Hatton, 1988;Rynes and Trank, 1999) and evolutionary genetics, biology and economics (Campbell, 1997;Duboule and Wilkins, 1998;Hirabayashi, 1996;Hirabayashi and Kasai, 1993;Jacob, 1977;Lavorgna et al, 2001). Baker and Nelson (2005) conducted an extensive review of this literature and found three main themes that were common across disciplines.…”
Section: Bricolagementioning
confidence: 99%
“…From its origins in anthropology, the notion of bricolage has proved useful in an extremely broad range of scholarly fields. Disciplines invoking use of Levi-Strauss's insights include-not surprisingly-anthropology (Chao, 1999;Dumont, 1996) and sociological ethnography (Denzin and Lincoln, 1994;Katovich, 1995;Weinstein and Weinstein, 1991), but also political science (Lanzara, 1998); women's studies (Gray, 1982), interpersonal relationships (Conville, 1997), complex information systems design (Lanzara, 1999), legal studies (Hull, 1991;Tushnet, 1999), education (Dent and Hatton, 1996;Hatton, 1988;Rynes and Trank, 1999) and evolutionary genetics, biology and economics (Campbell, 1997;Duboule and Wilkins, 1998;Hirabayashi, 1996;Hirabayashi and Kasai, 1993;Jacob, 1977;Lavorgna et al, 2001). Baker and Nelson (2005) conducted an extensive review of this literature and found three main themes that were common across disciplines.…”
Section: Bricolagementioning
confidence: 99%
“…The extent to which working-class youth are served or disadvantaged has remained, throughout the 150-year history of mass schooling in advanced capitalist economies, a central problem of social justice in education (Connell, 1993). Contemporary research on inequalities in educational provision, experience and outcomes, whether closefocus examinations of school life (Bettie, 2002;Dent & Hatton, 1996;Thompson, 2002) or broader examinations of access and institutions (Lynch & Lodge, 2002;Teese & Polesel, 2003), show that the class issue is far from being resolved.…”
Section: Introduction: Public Education and I T S Working-class Constmentioning
confidence: 99%
“…Although bricolage sometimes produces wonderful innovations such as the globally-competitive wind turbines studied by Garud and Karnoe (2003), it often provides only highly imperfect and temporary solutions. For example, use of bricolage by Australian primary school teachers was shown to result in poor academic success by their students (Hatton, 1989;Dent & Hatton, 1996). As several authors have noted, sometimes the results of bricolage may be simply stop gaps -for example innovative but temporary solutions that the organization fails or chooses not to adopt more broadly (Baker et al, 2003;Miner et al, 2001).…”
Section: Bricolage As Negativementioning
confidence: 99%